A clinical spectrum of dermatoses in dermatology outpatient department of paramilitary tertiary care center - Maharjan, Rupak; Karki, Alina; Maharajan, Rajendra; Shrestha, Mahendra Raj (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Dermatoses constitute a significant share of dermatology outpatient visits. However, data on their spectrum in tertiary care settings in Nepal are limited. This study examined the prevalence, patterns, and demographic distribution of dermatoses in a paramilitary tertiary care center. Method: This retrospective hospital-based study reviewed medical records of dermatology outpatients from January 2021 to December 2023. Data on age, gender, and clinical diagnoses were analyzed using SPSS version 17.00. Result: A total of 6,617 patients with dermatoses were analyzed. The age group 31–45 years was the most affected, comprising 2,417(37.34%) individuals of the total cases. Infective dermatoses were present in 3,437 (51.94%) patients. Among these, bacterial infections were the most common, affecting 1,143 (33.26%) patients. Within bacterial infections, the most frequent condition was folliculitis 501 (43.83%), followed by furunculosis 310 (27.12%). Viral dermatoses accounted for 571 (16.61%) cases, predominantly warts 301 (52.71%). Parasitic dermatoses were noted in 454 (13.21%) cases, primarily due to scabies 439 (96.70%). Non-infective dermatoses were seen in 3,180 (48.06%) patients, more common in females (1,637, 51.48%). The most prevalent noninfective condition was eczema (839, 26.38%). Among males, the most common infective dermatosis was fungal infections 587 (25.69%), and the predominant non-infective condition was eczema 482 (31.24%). In females, fungal infections 250 (21.70%) were the leading infective dermatoses, while hyperpigmentation 413 (25.23%) was the most common non-infective condition. Conclusion: Dermatoses in this paramilitary tertiary care center showed a diverse spectrum. Males were primarily affected by infective conditions like folliculitis, while females had more non-infective conditions, notably eczema and hyperpigmentation.